B Cell Depletion Eliminates FVIII Memory B Cells and Enhances AAV8-coF8 Immune Tolerance Induction When Combined With Rapamycin - Biswas, Moanaro; Palaschak, Brett; Kumar, Sandeep R. P.; Rana, Jyoti; Markusic, David M. (Frontiers in Immunology, 2020)
Hemophilia A is an inherited coagulation disorder resulting in the loss of functional clotting factor VIII (FVIII). Presently, the most effective treatment is prophylactic protein replacement therapy. However, this requires frequent life-long intravenous infusions of plasma derived or recombinant clotting factors and is not a cure. A major complication is the development of inhibitory antibodies that nullify the replacement factor. Immune tolerance induction (ITI) therapy to reverse inhibitors can last from months to years, requires daily or every other day infusions of supraphysiological levels of FVIII and is effective in only up to 70% of hemophilia A patients. Preclinical and recent clinical studies have shown that gene replacement therapy with AAV vectors can effectively cure hemophilia A patients. However, it is unclear how hemophilia patients with high risk inhibitor F8 mutations or with established inhibitors will respond to gene therapy, as these patients have been excluded from ongoing clinical trials. AAV8-coF8¬ gene transfer in naïve BALB/c-F8-/Y mice (BALB/c-HA) results in anti-FVIII IgG1 inhibitors following gene transfer, which can be prevented by transient immune modulation with anti-mCD20 (18B12) and oral rapamycin. We investigated if we could improve ITI in inhibitor positive mice by combining anti-mCD20 and rapamycin with AAV8-coF8 gene therapy. Our hypothesis was that continuous expression of FVIII protein from gene transfer compared to transient FVIII from weekly protein therapy, would enhance regulatory T cell induction and promote deletion of FVIII reactive B cells, following reconstitution. Mice that received anti-CD20 had a sharp decline in inhibitors, which corresponded to FVIII memory B (Bmem) cell deletion. Importantly, only mice receiving both anti-mCD20 and rapamycin failed to increase inhibitors following rechallenge with intravenous FVIII protein therapy. Our data show that B and T cell immune modulation complements AAV8-coF8 gene therapy in naïve and inhibitor positive hemophilia A mice and suggest that such protocols should be considered for AAV gene therapy in high risk or inhibitor positive hemophilia patients.